'Neuroendocrine' middle ear adenomas: consistent expression of the transcription factor ISL1 further supports their neuroendocrine derivation. Issue 2 (10th November 2014) - Agaimy, Abbas; Lell, Michael; Schaller, Tina; Märkl, Bruno; Hornung, Joachim
<x xml:space="preserve">Abstract</x> Aims Neuroendocrine middle ear adenoma (MEA) is a rare epithelial neoplasm of uncertain histogenesis that frequently shows neuroendocrine features. To date, <120 cases have been reported. The aims of the current study were to describe our experience with neuroendocrine MEA, to assess the frequency of specific neuroendocrine differentiation, and to test these lesions for transcription factors known to be expressed in a variety of other neuroendocrine tumours. Methods and results We investigated six cases of neuroendocrine MEA, and stained them, for the first time, for the transcription factors CDX2, TTF1, PAX8, and ISL1 (islet‐1). The patients were four men and two women (mean age, 39 years; range, 27–53 years). Two of four patients with extended follow‐up (4.5–22 years) experienced recurrence at 92 months, and at 9 and 22 years, respectively. One case extending into the external ear coexisted with cholesteatoma. Histological examination showed trabecular, solid, acinar, glandular, cribriform, organoid, nested, diffuse non‐cohesive plasmacytoid and pseudoalveolar patterns in varying combinations. Immunohistochemistry showed consistent expression of vimentin (4/4), pancytokeratin (6/6), synaptophysin (6/6), CD56 (4/4), and ISL1 (6/6). A CK7 antibody stained scattered cells in two of five cases. The myoepithelial markers and transcription factors TTF1, CDX2 or PAX8 were not expressed in any of the cases. Conclusions Middle ear adenoma is an indolent, locally recurring, but generally non‐metastasizing neoplasm with uniform expression of synaptophysin and ISL1, indicating true neuroendocrine differentiation. Because of its highly varied cellular and architectural appearance, MEA should be distinguished from tympanic paraganglioma and a variety of rare benign and malignant lesions at this site.